Serments en filigrane et conflits de loyauté dans Love Intrigues (1713) de Jane Barker - Constance Lacroix (Etudes Epistémè)
Oath-taking – or not taking – and religio-political commitment play a significant, if often overlooked part, in Jacobite writer Jane Barker’s life and works (1652-1732), since her 1673 and 1678 encounter with the Test Act, as allegorically recalled in her autobiographical manuscript poetry, an ordeal which jeopardized the positions of this open-minded high-church Cavalier’s daughter’s beloved recusant relatives and much–admired Duke of York. Converting to Catholicism in 1685 in fulfillment of a vow to the Virgin, Jane Barker further embraced a cause which would lead her in a fifteen-year-long exile in France after 1689, then submitted her, when back in England, to many stoically-endured persecutions and legal constraints, and turned her all the while into a stubborn opponent to oaths of allegiance to the new regime. It is not to be wondered therefore that vows, oaths and various forms of verbal and non-verbal commitments should potently, if subtly, wind their way into and through Jane Barker’s first semi-autobiographical novel Love Intrigues or the History of the Amours of Bosvil and Galesia (published 1713, then revised as The Amours of Bosvil and Galesia in 1719). Bosvil and Galesia’s unsuccessful love affair, as told by Galesia to her friend Lucasia in Saint-Germain, might indeed be traced to three main causes, buried under a layer of psychological considerations and small narrative events which forestalls censorship while allowing for deep insights into the human psyche : Galesia’s firm refusal to enter into any sort of contract with or to bind herself by any promise to her enterprising, altogether too apt to dispense with paternal authority, cousin-lover ; Bosvil’s manifold, by no means unnoticed and unresented perjuries, and Galesia’s early vow of celibacy to the Muses, who pledge themselves to reward their votary with a career similar to royalist poetess Orinda’s. An invaluable tool to appreciate Jane Barker’s literary Jacobitism, her subdued yet insinuating variations on oaths and vows shed a new light on that short amatory piece, too often dismissed as a first attempt at creating an “impeccably respectable” (female) novelistic brand or merely construed as a protofeminist protest sharpened into pre-richardsonian psychological realism : set against the background of (required and rejected) post-1689 oaths of allegiance and abjuration, Love Intrigues emerges as an imaginative conflict between two conceptions of the meaning of oaths and political power, conveying a powerful entreaty that actually wavering Recusants, Tory-Jacobite and Non-Jurors should immure themselves in unflagging mutism and constant fidelity to their previous “vows” to James and his de jure heir.